2014
DOI: 10.1177/0018720814531784
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Key Size of Touch Screen Virtual Keyboards on Productivity, Usability, and Typing Biomechanics

Abstract: We evaluated the effects of virtual keyboard key sizes on typing force exposures, muscle activity, comfort, and typing productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 51 publications
1
23
1
Order By: Relevance
“…The results of Kim et al (2014) imply that prolonged use of touch screen keyboards potentially increase the risk of experiencing musculoskeletal discomfort and affect muscle groups (as a result of this static loading) in wrist and shoulder regions. Zunjic et al (2015) discussed the factors that affect the quality of education such as the dimensions of school furniture with respect to the students' anthropometric properties, and conclude that a comfortable working environment (air conditioning, illumination, etc.)…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of Kim et al (2014) imply that prolonged use of touch screen keyboards potentially increase the risk of experiencing musculoskeletal discomfort and affect muscle groups (as a result of this static loading) in wrist and shoulder regions. Zunjic et al (2015) discussed the factors that affect the quality of education such as the dimensions of school furniture with respect to the students' anthropometric properties, and conclude that a comfortable working environment (air conditioning, illumination, etc.)…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the T5 tap‐typing task, compared with the lowest error rate (7.7%) for the smallest key spacing of 15 mm squared in Kim's study () with 14‐in. display settings and the significantly decreased error rates (from 2.4% to 1.0%) as key spacing increased (from 13.5 × 8.7 to 27.5 × 17.0 mm) in Tao's study () with 23‐in.…”
Section: Resultsmentioning
confidence: 70%
“…Third, regarding the tap‐typing tasks, the display size effects interactively strengthen the key size/spacing effects induced by the discrepancies of these sizes. Compared with the studies with larger display sizes in the studies of Kim et al () and Tao et al () (14‐in. [347 × 248 mm] and 23‐in.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning device size or key size, some researches have reported that smaller key sizes on software/virtual keyboards reduce the data entry speed and accuracy [4]- [6]. Although the above researches targeted sighted people, the same tendency may be derived from blind users, or touching small objects may become more difficult for them.…”
Section: Introductionmentioning
confidence: 99%